A primer on in vivo cell tracking using MRI - Cheng, Hai-Ling Margaret (Frontiers in Medicine, 2023)
Cell tracking by in vivo magnetic resonance imaging (MRI) offers a collection of multiple advantages over other imaging modalities, including high spatial resolution, unlimited depth penetration, 3D visualization, lack of ionizing radiation, and the potential for long-term cell monitoring. Three decades of innovation in both contrast agent chemistry and imaging physics have built an expansive array of probes and methods to track cells non-invasively across a diverse range of applications. In this review, we describe both established and emerging MRI cell tracking approaches and the variety of mechanisms available for contrast generation. Emphasis is given to the advantages, practical limitations, and persistent challenges of each approach, incorporating quantitative comparisons where possible. Toward the end of this review, we take a deeper dive into three key application areas – tracking cancer metastasis, immunotherapy for cancer, and stem cell regeneration – and discuss the cell tracking techniques most suitable to each.